PT Merpati Nusantara Airlines Bankruptcy Case Study Under Law - Metta Valoka; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Bankruptcy is something that occurs when a company is unable to pay all its debts in any form and is no longer able to compete in the community. This case study discusses the bankruptcy of a company engaged in the aviation sector, namely PT Merpati Nusantara Airlines. In this journal, the author uses qualitative methods by taking data from books, internet news articles, and other sources related to this journal. Based on the journal made by the author, it will tell what caused Merpati Airlines to experience bankruptcy, bankruptcy which is reviewed based on the law on Bankruptcy and Suspension of Obligations for Payment of Debt Number 37 of 2004 and how solutions for other companies not to experience the same thing as Merpati Airlines .